Advantages and Disadvantages of Online Teaching from Teachers' and Parents' Perspective - Мarija M. Cvijetić; Мia R. Marić; Мila B. Beljanski (University of Belgrade, Teacher Education Faculty, 2022)
The corona virus pandemic has brought online teaching and distance learning to the forefront, which is very different from typical classroom teaching. The aim of this paper was to determine the differences in the perception of the advantages and disadvantages of online teaching between primary school teachers and parents of primary school children. The sample consisted of a total of 1120 respondents, out of which 570 are teachers employed in primary schools (50.9%) and 550 (49.1%) are parents of children attending primary schools in Serbia. A questionnaire was created for the purposes of this research and it was applied in an online form. The results of this research show that the perception of the perceived advantages and disadvantages of online teaching and distance learning from the teachers' and parents' point of view differs significantly, and that teachers have a more intense experience, both in terms of advantages and disadvantages of this type of teaching process. According to both parents and teachers, the most significant disadvantage of online teaching is the lack of direct contact with pupils. From the obtained results it is possible to conclude that a step forward is needed in terms of further development of teacher competencies and resources for new professional challenges, as well as in terms of guiding and empowering parents for a more active role in the process of online education of their children.